Editorial: Towards Commercialization of African Traditional Medicines (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Many years ago, back in my village, I regularly used juice from freshly-cut leaf of Croton macrostachyus, on bleeding wounds. The bleeding would stop and the wound healed without any other intervention. Croton macrostachyus is a common plant in Kenya which is still used by local people as a herbal remedy. The leaf juice is yet to be formulated into a pharmaceutical product with commercial applications. In this issue of the journal, Usifoh et al. have described the formulation of Chrysophyllum albidum extract into a topical cream for the treatment of dermatological infections.